The Legal Challenges of International Electronic Contracts in Iraq - Aziz, Zana Ismael; Ayub, Zainal Amin; Mohamed, Khadijah (Academic Research Publishing Group, 2017)
The electronic commerce activities raise emerging legal challenges and problems based on the existing legal systems in Iraq. The traditional commercial relations make the commercial activity on the basis of offer and acceptance relies on the commitment of the seller. For example, to deliver the sales physically and the buyer has to pay the price either in cash or by using tools that are alternative to direct payment-in cash through trade securities or other means of conventional banking fulfillment. However, it is a different story in relation to electronic commerce transactions. The difference is not only in the concept of the commercial activity but also in the tools of its practice and the nature of relations arising under its umbrella. Most activities in the e-commerce activities is carried out online i.e. through the internet or information network. The use of technology is dominant, creating new challenges against the existing legal systems in Iraq. The aim of this article is to study the challenges and problems with regards to electronic contracts in Iraq. It is found that the current law governing the e-commerce in Iraq is the main obstacle for Iraqi consumers to conclude such contracts despite growing importance of e-commerce contract among Iraqis in their daily life. The article suggests amendment to the current legislation governing e-commerce to facilitate the growth of online transaction in Iraq